Respon Petani Tembakau Terhadap Kegiatan Pengembangan Model Usahatani Partisipatif (PMUP) di Desa Tlahab Kecamatan Kledung, Kabupaten Temanggung - Arfianto, Andrie (Magister Pembangunan Wilayah dan Kota,Undip, 2012)
Participatory Farming Model Development (Pengembangan Model Usahatani Partisipatif â€ PMUP) conducted by the government in Desa Tlahab was intended to improve the farmer welfare by increasing income without sacrificing the heritage of tobacco farming culture while reducing the environmental damage caused by tobacco cultivation. This kind of agricultural activities need immense participation and willingness of the farmers as a supporting response for the implementation of this system on their land. Farmers stated that living conditions have kept them from supporting the implementation of PMUP. This condition includes farmer socioâ€economic situation, environmental conditions in carrying out the activities, the low performance of farmer groups, lack of competitiveness of the PMUP compared to previous agricultural system, also lack of performance from the institutional boards.